Analysis of The Hadith About The Permissibility of 'Azl - Nuraini, Dewi Fauziah (PT. Sharia Journal and Education Center, 2024)
ABSTRACT This research focuses on studies related to 'azl practice, in the analysis if it is related to the hadith and its explanation as well as the purpose of 'azl preventing, controlling, limiting pregnancy aimed at a benefit are permitted human efforts, but the success of these efforts is within the control of Allah SWT. If a pregnancy is destined by Allah, then it will happen, no matter how much effort is made to prevent it, there is nothing in vain from this effort, if you reject it, then you reject what Allah SWT. has been destined, indeed Allah SWT. All-knowing, all-wise, Allah SWT. knowing what humans don't know. Keywords: 'Azl Practice, Controlling, Limiting Pregnancy ABSTRAK Penelitian ini terfokus pada kajian terkait praktik ‘azl, dalam analisisnya jika dikaitkan dengan hadits dan penjelasannya serta tujuan dari ‘azl, mencegah, mengontrol, membatasi kehamilan yang ditujukan untuk suatu maslahat itu adalah usaha-usaha dari manusia yang diperbolehkan, namun keberhasilan dari usaha tersebut ada didalam kendali Allah Swt., jika ditakdirkan oleh allah sebuah kehamilan, maka terjadilah, walau sebesar apapun usaha untuk mencegahnya, tidak ada yang sia-sia dari usaha tersebut, jika menolaknya, maka menolak dari apa yang Allah Swt. telah takdirkan, sesungguhnya Allah Swt. maha mengetahui lagi maha bijaksana, Allah Swt. mengetahui apa yang tidak manusia ketahui. Kata Kunci: Praktik ‘Azl, Pengontrolan, Pembatasan Kehamilan